Dimensions of Sports in the Meti Kei Dance - Pieter, Marsiline; Tahapary, J. (SAINTIS Publishing, 2024)
This study aims to understand the social phenomena that in Meti Kei Dance exist in the Community of Southeast Maluku. This was a qualitative study using the qualitative descriptive design. The results of the study show that the Meti Kei dance in the community of Southeast Maluku is a cultural heritage from the ancestors growing on the basis of some folk tales. The Meti Kei dance growing rapidly nowadays is a result of the development made by artists who create folk songs. Many positive values can be derived from both the traditional and the modern Meti Kei dance. The values include mutual respect, cooperation, and unity upholding. In addition to having such values, the dance has a potential to enhance the social interaction in the community and can improve people’s physical fitness with particular requirements. Based on the explanation about dimensions of sports in the Meti Kei dance, namely philosophical, sociological, and physiological dimensions, it can be recommended as a form of sport for the community or a recreational sport that can be done whenever and wherever by all social strata.